2014
DOI: 10.1097/01.tp.0000438636.52085.50
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Anti-HLA Antibody-Dependent Natural Killer Cell Activation by Immunosuppressive Agents

Abstract: These results suggest that potent suppressive effects of CNIs and prednisone on antibody-mediated NK cell activation may contribute to the reduction of ADCC in sensitized patients and possibly reduce the risk for ADCC-mediated ABMR. These further underscore the importance of medication compliance in prevention of ABMR and possibly chronic rejection, and suggest that ADCC-mediated injury may increase in strategies aimed at CNI or steroid minimization or avoidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
(25 reference statements)
1
28
0
Order By: Relevance
“…7-10 In this study, we assessed a possibility that other CD16 bearing cells, monocytes, and CD8+ T cells, were capable of antibody-mediated cell activation, resulting in cytokine production in the in vitro ADCC. We found that, IFNγ, TNFα, and IL-6–producing cells were significantly elevated in the ADCC compared to MLR and controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7-10 In this study, we assessed a possibility that other CD16 bearing cells, monocytes, and CD8+ T cells, were capable of antibody-mediated cell activation, resulting in cytokine production in the in vitro ADCC. We found that, IFNγ, TNFα, and IL-6–producing cells were significantly elevated in the ADCC compared to MLR and controls.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Briefly, pooled PBMCs isolated from blood of 5 normal individuals and then irradiated (PBMCx) were preincubated with HS (ADCC condition) or normal sera (NS, mixed lymphocyte reaction [MLR] condition), and the antibody-coated PBMCx were used as stimulator cells. HS sera was prepared by pooling sera from 70 end-stage renal disease HS patients with PRA greater than 50% and the same HS sera was used for all experiments in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human studies, NK-cell transcripts and intravascular accumulation of NK cells have been detected in kidney allografts with DSA and C4d negative chronic AMR (74). Shin and colleagues recently have shown that the calcineurin inhibitors, tacrolimus and cyclosporin A, in combination with prednisone synergistically suppress NK cell IFNγ production and degranulation significantly more than anti-metabolites, such as sirolimus or mycophenolate mofetil (75) (Figure 1). Given the NK cell signature of AMR in experimental models and in patients, it is possible that NK cells can be used as yet another tool to identify C4d negative rejection and may represent a therapeutic target to ameliorate AMR.…”
Section: Hla Class I Antibody Leukocyte Recruitment and Activationmentioning
confidence: 99%
“…IFN-γ production by NK cells can be triggered by allogeneic target cells coated with alloantibody (139), and contributes to chronic rejection in murine models (129). Current immunosuppressive drugs incompletely inhibit NK cell-mediated alloreactivity (140).…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 99%